A New Framework for the Pleistocene Stratigraphy of the Central St. Lawrence Lowland, Southern Québec - Lamothe, Michel (Géographie physique et Quaternaire, 1989)
ABSTRACTFor three decades, a stratigraphic framework involving one glaciation with two major ice advances (represented by the Bécancour Till and Gentilly Till), separated by one brief interstade (represented by the St. Pierre Sediments), has been invoked to explain the lithostratigraphic succession of Pleistocene sediments exposed in the St. Lawrence Lowland of southern Québec. New exposures found along the bluffs of the St. Lawrence River and recent borehole data provide evidence that the Pleistocene depositional sequence is the result of three glacial advances and two nonglacial events, each represented by organic-bearing units. Two lithostratigraphic units (Lotbinière Sand and Lévrard Till) and three climatostratigraphic units (St. Lawrence Stade, Grondines Interstade and Les Becquets Interstade) are introduced in the stratigraphie nomenclature. No definite age can be assigned to the lowermost till (Bécancour?) but it is now believed to be pre-Sangamonian. Field observations and geochronological data suggest the lower and upper interstadial sediments, and an intervening glacial unit represent brief but severe environmental changes that occurred at the beginning of the Wisconsin Glaciation, ca. 90-70 ka BP. This sequence may correlate with marine isotope stage 5a, stage 4, and the earliest part of stage 3. The age of the onset of the last glacial advance (Gentilly Till) is problematic, possibly ranging from 60 to 30 ka BP.